Overlapping and divergent signaling pathways for ARK1 and AGD1 in the control of root hair polarity in Arabidopsis thaliana - Yoo, Cheol-Min; Blancaflor, Elison B. (Frontiers in Plant Science, 2013)
We previously showed that seedlings harboring mutations in genes encoding ARK1, an armadillo repeat-containing kinesin, or AGD1, a class 1 ARF-GAP, have root hairs that exhibit wavy/spiral growth and two tips originating from one initiation site. These root hair defects were accompanied by bundling of endoplasmic microtubules and filamentous actin (F-actin) that extended to the extreme root hair apex. The similar phenotypes of ark1 and agd1 mutants suggest a tight coordination between the cytoskeleton and membrane trafficking in the control of root hair polarity. Indeed, cell biological and genetic studies of the agd1 mutant provided evidence that AGD1’s involvement in root hair development involves cross-talk among phosphoinositides (PIs), the actin cytoskeleton and other small GTPases such as ROP2 and RABA4b. Here we show that ark1 root hairs mirror those of agd1 with regard to altered targeting of ROP2 and RABA4b, as well as abnormal tonoplast organization. Furthermore, like agd1, enhanced root hair defects in double mutants in ARK1 and genes encoding a type B phosphatidylinositol-4-phosphate 5-kinase 3 (PIP5K3), a phosphatidylinositol-4-phosphate (PI-4P) phosphatase (RHD4), a phosphatidylinositol transfer protein (COW1), and a vegetative actin isoform (ACT2), were observed. However, root hair shape of some ark1 double mutant combinations, particularly those with act2, pip5k3 and rhd4 (ark1 act2, ark1 pip5k3, ark1 rhd4), differed in some respects from agd1 act2, agd1 pip5k3 and agd1 rhd4. Taken together our results continue to point to commonalities between ARK1 and AGD1 in specifying root hair polarity, but that these two modulators of tip-growth can also regulate root hair development through divergent signaling routes with AGD1 acting predominantly during root hair initiation and ARK1 functioning primarily in sustained tip growth.